Hot melt adhesives prepared by grafting of acrylic and crotonic acids onto metallocene ethylene–octene copolymers. (July 2019) - Pavlinec, Juraj; Novák, Igor; Rychlý, Jozef; Kleinová, Angela; Nógellová, Zuzana; Preťo, Jozef; Vanko, Vladimír; Žigo, Ondrej; Chodák, Ivan
Commercial metallocene ethylene–octene random copolymer, Resinex PE RXP 1502 (RXP), was grafted with acrylic or crotonic acid in the solution and in the melt to increase the RXP's polarity and adhesion to cellulose-based substrates. Acrylic or crotonic acids were grafted on the RXP macromolecules which were activated with an oxygen–ozone mixture. The formed graft copolymer was tested as additive to a hot melt adhesive (HMA) improving adhesive properties. The most effective procedure was to graft RXP with acrylic acid in the melt, while grafting activated RXP in a toluene solution was less efficient. The melt grafting efficiency is high and varies between 0.77 and 0.97. The RXP polarity after grafting increases significantly, as there is a 15% decrease in the water contact angle and an increase in the surface energy and its polar component by 1.1–1.7 times as compared to the virgin RXP. The heat-fail temperature resistance in peel of RXP grafted with acrylic and/or crotonic acid increased by more than 10°C, while the heat-fail temperatures of adhesive joints in shear tests were similar. The adhesive joint peel strength increased 1.2 times. The cardboard–HMAs based on virgin RXP adhesive joint peel tests exhibit adhesive failure, whereas the cardboard–HMAs containing grafted RXP joints show cohesive failure.